Adaptive preview control with deck motion compensation for autonomous carrier landing of an aircraft. (11th March 2021) - Bhatia, Ajeet Kumar; Jiang, Ju; Kumar, Aakash; Shah, Syed Awais Ali; Rohra, Avinash; ZiYang, Zhen
Abstract: In this article, an autonomous carrier landing problem of an aircraft is addressed by developing an autonomous carrier landing system (ACLS) composed of previewable guidance and control systems. In the guidance system, an appropriate touchdown point is estimated by predicting the seakeeping motion of the deck by unscented Kalman filtering technique, which is then utilized to adjust the reference glide path and produce an effective deck motion compensation, indispensable for a safe landing. The adaptive preview control (APC) scheme is proposed, which utilizes future reference information. The feedback and feedforward adaptive gains are derived through the Lyapunov stability theorem ensuring better tracking response and disturbance rejection. Hence, the asymptotic stability of the closed‐loop system is guaranteed. The simulation results depict better performance of the proposed ACLS in the presence of deck fluctuations and airwake disturbance compared with PID and LMI based preview control schemes.